The Influence of the Sociodrama Method on the Speaking Ability of Grade V Students of SDN 1 Gerung Utara for the 2022/2023 Academic Year - Fatimatul Ulya; Muhammad Tahir; Abdul Kadir Jaelani (International Journal of Social Service and Research, 2023)
This study aims to determine the influence of the socio-drama method on the speaking ability of grade V students of SDN 1 Gerung Utara for the 2022/2023 school year. This type of research is Quasi Experimental Design research type Nonequivalent Control Group Design. The population in this study was all grade V students of SDN 1 Gerung Utara. The sampling technique used was saturated sampling with a sample of 27 students of class V A as a control class and 28 students of class V B as an experimental class. Data collection techniques in this study are tests (pre-test and post-test) and observation. The researchers' data was analyzed with the help of SPSS. 16. The researcher hypothesis examiner uses the calculation of the Independent Test Sample Test. The results showed the intention of sig. (2-tailed) 0.001 < 0.05, then H0 is rejected and Ha is accepted or there is a significant influence with the socio-drama method on the speaking ability of grade V students of SDN 1 Gerung Utara for the 2022/2023 school year.